HPV and cervical cancer - Petry, Karl Ulrich (Scandinavian journal of clinical & laboratory investigation. Supplement, 2014)
Abstract In recent analyses of the global burden of cancer among women, cervical cancer ranked second to breast cancer. Numbers of new cervical cancer cases are increasing constantly although this tumor is one of the best preventable malignancies of all relevant human cancers. The genesis of cervical cancer depends essentially on an infection of the uterine cervix with human papillomavirus (HPV) that needs to persist for many years and decades. Oncogenic cell transformation occurs almost exclusively in a discrete cell population at the squamous columnar junction (SCJ). These peculiarities enable primary prevention with HPV-vaccination as well as secondary prevention by detecting and treating true precursor lesions. The actual screening program with annual cytology smears is already effective but results in a high number of false positive results and unnecessary treatments. Based on a good understanding of the etiology and high evidence from large randomized controlled trials a significant improvement in the prevention of cervical cancer by shifting to HPV screening in women aged 30 years or older is feasible. This would result in a further reduction of new cancer cases by 70-80 % with less screening examinations and interventions when well-defined patient pathways are followed and colposcopy in accordance with international quality standards is used as the gold standard for the minimal invasive management of abnormal findings. HPV vaccination prevents the development of approximately 80 % of true precursors and should have a similar impact on the incidence of cervical cancer. A combination of HPV vaccination and screening could almost eradicate cervical cancer and reduce the burden of other tumors and diseases related to HPV.